A Case Study of Using Metacognitive Reflections to Enhance Writing Skills and Strategies in an Agricultural Media Writing Course - Tobin Redwine; Holli R. Leggette; Brooke Prather (Journal of Applied Communications, 2017)
Writing is a foundational skill in agricultural communications, and metacognition the learning and understanding of such skill. Integrating reflection into a writing course is one way to enhance students’ metacognition and metacognitive awareness as reflection provides writers an opportunity to become a critic of their writing experiences. However, what happens when students reflect on their metacognitive awareness during and throughout the writing process? Using a qualitative and quantitative content analysis, we interpreted 16 students’ metacognitive writing reflections at four points in an advanced media writing course. We identified and analyzed emergent themes from the reflections and measured the frequency of each theme over the duration of the course. Three major themes emerged: a) metacognitive awareness of writing skills, b) metacognitive awareness of writing strategies, and c) metacognitive awareness of knowledge transfer. A total of 13 sub-themes were identified further characterizing the themes. Interviewing (a writing skill) emerged more in the third reflection than any other time, and revision (a writing strategy) emerged more at the beginning and end of the course than in the middle. Additionally, participants reflected less about outcomes (a component of knowledge transfer) at the end of the course and more about their plans for the future. Findings support the value of metacognitive reflections as a transformational instruction tool. Practitioners and writing instructors in agricultural communications should be cognizant of skills, strategies, and knowledge transfer as they plan and implement writing education and be adaptive and flexible to meet students’ changing metacognitive awareness.
Keywords: Media Writing; Metacognition; Reflection; Writing Skills and Strategies